Biological activity of Spirogyra on Candida albicans and Leishmania tropica - كورجك, فردوس; سيراؤوس محمد (Latakia University Journal -Biological Sciences Series, 2024)
Three species of Spirogyra moss, S. variformis, S. fluviatilis, and S. crassa, were collected from the Derverver and Hour Ain areas in the Damascus countryside governorate, Extraction was carried out with methanol and chromoform solvents, and the total content of phenols and flavonoids was measured. The effect of varying concentrations of the extracts on Candida albicans and the Leishmania tropica parasite was studied. The highest content of phenols reached 236.60 ± 0.89 mg/g, and flavonoids reached 86.47 ± 0.14 mg/g in the methanolic extract of S.fluviatilis. The largest diameter of the inhibition corona was determined to be 24.5 ± 0.5 mm at a concentration of 60 mg/g of the methanolic extract of S. fluviatilis on C. albicans. While the half maximal inhibitoy concentration (IC50) of the Leishmania parasite L. tropica was less than 125 µg/ml of the methanolic extract of S. fluviatile after 48 hours, the half maximal inhibitoy concentration (IC50) of the species S. variformis ranged between 500 and 750 µg/ml, and the concentration value was The IC50 for S. cracca is higher than 750 µg/ml at the same time.